Developing a pulsar-based time standard. (5th March 2015) - Hobbs, G.
Abstract: We describe how observations of pulsars from the Parkes Pulsar Timing Array (PPTA) project have been used to develop a pulsar-based timescale. This is the first such timescale that has a precision comparable to uncertainties in international atomic timescales.